Click Here if You Agree (to Reclaim the EdTech Classroom through Speculative Co-design) - Wieczorek, Michał; Costello, Eamon (Proceedings of the International Conference on Networked Learning, 2026)
Any examination of new educational technologies should look beyond the hopes, dreams and promises that inevitably follow in their wake. To fully understand the impact of new tools on teaching and learning, we must also identify what will have been lost and what will have been surrendered when the next shiny thing is (chosen to be) implemented. This workshop seeks to critically examine the language that is used to describe, market and push technologies into the classroom, which is also a language that surrenders our choices, diminishes our agency, and limits the scope of our imagination to the visions pushed by the powerful few. We propose speculative and creative approaches for introducing critical and deeper conversations on edtech in the classroom. Teachers and student teachers encounter a wide variety of voices and registers through which edtech is promoted, criticised and implemented in their schools, which leads to tonal and conceptual dissonances that are difficult to navigate. Edtech products are introduced through optimistic marketing materials and hype that do little to illuminate the actual workings of technology (Wieczorek & Romele, 2025). What exactly does AI-powered personalisation mean? Why does learning require a revolution? What ideas about learning stand behind the visions spun by edtech marketers? Such hype-driven language is in stark contrast to the highly technical and legalistic wording found in terms of service, privacy policies and user manuals that accompany (and obfuscate) edtech’s everyday use. These make it clear that the glorious future is open only to those willing to enter on tech companies’ own terms and conditions. We created this workshop as a space for exploring how we could bring these different registers, tonalities and discourses together. Building on our experiences with initial teacher education, teacher professional development courses and critical edtech methods (Wieczorek, 2025a; Costello et al., 2025; Costello et al., 2023; see also Gidiotis & Hrastinski, 2024; Hrastinski & Jandrić, 2023; Rahm, 2024), we present our ideas for discussing edtech marketing and terms of use with student teachers in a way that exposes the values, intentionalities and power relations hidden behind them. We demonstrate this through a creative activity asking participants to describe tools present in every classroom – blackboards, desks, pens, paper, etc. – through the language that is currently being used to describe (and obfuscate) new edtech products. What hopes might we have once held for everyday teaching aids and learning materials? What licensing agreements do we need to accept to ensure that we use this old-school tech responsibly and for intended purposes?